REVIVING KHADI: EXPLORING SUSTAINABLE QUALITIES AND PROMOTING KHADI AMONG FASHION DESIGN STUDENTS - Dhillon, Avninder Kaur; Kapoor, Nandini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper delves into the revival of Khadi within the fashion industry, focusing on its sustainable qualities and promotion among fashion design students. Khadi, historically significant for its association with India's independence movement, embodies values of self-reliance, sustainability, and cultural heritage. The objectives include raising awareness among students about sustainable perspective of Khadi, motivating them to explore it creatively, and evaluating its acceptance among consumers, and young generation. The methodology encompasses literature review, interviews, educational workshops, design projects, market testing, and analysis. Key findings emphasize Khadi's enduring relevance, educational intervention, effectiveness, and the market potential of Khadi-based collections with embellishment art. Recommendations include curriculum integration, interdisciplinary collaboration, research and innovation support, industry partnerships, promotional campaigns, and educational resources.